Developing E-Learning System to Support Teaching and Learning Activities Using DSDM Approach - Ahmad Kevin Prawira; Tanika D Sofianti; Yuki Indrayadi (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2015)
Nowadays academic institutions have to follow development of technology to give high accreditation in education. Development in Information technology is considered as one of the leading factor that affecting the changes in higher education academic institution, especially through E-Learning system. The main objective of this research is to design how to develop E-Learning system in teaching and learning process at Industrial Engineering Department of Swiss German University, by using Dynamic System Development Method (DSDM). The developed E-Learning that is being tested by developer and user to be analyzed and assessed is called Moodle. The result shows that the teaching and learning processes can be well improved by integrating the developed E-Learning system including its specific interfaces and platform. It also shows that the developed system is also well accepted by potential users, as indicated by the user acceptance test. The result of the research is analyzed by using the descriptive analysis to reveal the capability of the system. It shows that developed E-Learning system is capable to be implemented in Industrial Engineering Department, provided that the infrastructure is also prepared to support such system.